Improving the Students’ Reading Comprehension Through Skimming Technique at the Second Grade of SMP Negeri 3 Batuputih - Ivo Astri (Journal of Teaching and Education, 2022)
This research was designed to improving students’ reading comprehension through skimming technique at the second grade of SMP Negeri 3 Batuputih. The problem of the research was “How can skimming technique improve the students’ reading comprehension at the second grade of SMP Negeri 3 Batuputih?”. The objective of the research are as follows: (1) Generally, the objective of this research was to describe the students' improvement in reading comprehension through skimming technique at the second grade of SMP Negeri 3 Batuputih. (2) Specifically, the research was to increase students’ reading comprehension in each cycle of the second grade students of SMP Negeri 3 Batuputih. Design of this research was collaborative classroom action research which was preceded by setting up plans, implementation, observation, analyzing, and reflection. This research was conducted in two cycle.The data of this research was obtained from the result of reading test and observation sheets. They were taken during the implementation of the action. The finding of this research show that skimming technique could improve the students’ reading comprehension. The improvement could be described on the average score of the students. In the first cycle based on students’ reading test 48% students have met criteria of success, in other words 12 of 25 students in the classroom got score 75 or more. It means 52% of students have failed. It was supported by the average score of students activity based on observation sheets in first cycle was 4.24 in first meeting, improve 5.44 in second meeting, and become 6.84 in the third meeting. It means that they were still on enough category.On cycle two based on the students’ reading test in second cycle 88% students got score 75 or more and 12% students got score less than 75. In other words, 22 students got score 75 or more and 3 students got score less than 75. It means, 88% students have met the criteria of success and 12% students have failed. It was supported by the average score of students activity based on observation sheets was 8.24 in first meeting improve 9.12 in second meeting and become 10.48 in the third meeting. It means that they were on good category.Finally, it is recommended for the English teacher to apply this technique as one of the alternatives that could be used in teaching reading because this technique could improve the students’ reading comprehension.